2018
DOI: 10.1159/000484627
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Thrombocytopenia after Self-Expandable Transcatheter Aortic Valve Replacement: A Single-Center Experience from China

Abstract: Objectives: The importance of thrombocytopenia (TP) has been discussed previously. However, data are still limited, especially on predictors of TP. We sought to investigate predictors of TP after transcatheter aortic valve replacement (TAVR), in particular, clinically significant TP. Methods: We reviewed a total of 123 consecutive patients undergoing TAVR in our medical center. They were stratified into 3 groups according to the nadir platelet count post-TAVR: no/mild TP, moderate TP, and severe TP. Clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In the last few years, several TAVI-rTP investigations were conducted, mostly on Core-valves and some on Sapien valves [6][7][8][9][10][11][12] and only one study compared between the two types of expandable systems. 13,14 These studies include heterogeneous TAVI indications and different technologies, comparable to our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last few years, several TAVI-rTP investigations were conducted, mostly on Core-valves and some on Sapien valves [6][7][8][9][10][11][12] and only one study compared between the two types of expandable systems. 13,14 These studies include heterogeneous TAVI indications and different technologies, comparable to our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TAVI has evolved to be simpler and safer 4‐5 . TAVI related thrombocytopenia (TAVI‐rTP) is a common periprocedural finding 6‐8 . A decrease in platelet count appears in nearly 90% of the treated patients 9 and the severity of this phenomenon has been associated with worse clinical outcomes 10‐14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence demonstrated that thrombocytopenia is inevitable after transcatheter aortic valve replacement (TAVR) (1)(2)(3)(4), and that severe thrombocytopenia are significantly associated with worse clinical outcomes (1)(2)(3)(5)(6)(7)(8). With the development of TAVR technology, TAVR is an established treatment for selected severe symptomatic aortic stenosis (AS), and its safety and efficacy in patients with aortic regurgitation (AR) has also been explored (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Transcatheter aortic valve implantation (TAVI) related thrombocytopenia (TAVI-rTP) is a common periprocedural finding [1][2][3]. Flaherty et al coined the concept that TAVI-rTP may be a "universal and virtually inevitable" phenomenon [4].…”
Section: Introductionmentioning
confidence: 99%